Design research methods with elderly participants: an analysis from the PPGDg- -UFMA studies - Xavier, Alessandra Maria de Aguiar; Serra, Mayanne Camara; Campos, Lívia Flávia de Albuquerque; Maia, Ivana Marcia Oliveira (DAT Journal, 2021)
This article seeks to reflect on the importance of design research aimed at the elderly, aiming to analyze the methods and techniques most used in usability research with this public, based on research carried out in the Master’s Program in Design (PPGDg) from the Federal University of Maranhão (UFMA) in the Design Line: Ergonomics and Usability of Products and Systems. The methodology used was the unsystematic bibliographic survey carried out on the program’s dissertations, of which four studies were selected that bring the participation of elderly people. The research allowed knowledge of the methods and techniques most frequently used in studies involving the elderly, with an emphasis on interviews, questionnaires and group activities on occasions when participants verbalize perceptions and help in producing recommendations for artifacts.